Macroeconomic effects of the gender revolution - Drago Bergholt; Luca Fosso; Francesco Furlanetto (Norges Bank, 2024)
U.S. labor market data exhibit a major, secular decline in the employment and wage gaps between males and females. In this paper, we identify the underlying, structural forces and quantify the spillover from this gender convergence to the broader macroeconomy. A novel time series model maps empirical trends in data into (aggregate and gender-specific) structural trends. Identification is achieved with restrictions derived from a neoclassical model with gender-specific labor. Empirically, we find that secular changes in female-specific labor productivity account for approximately one-third of economic growth in the postwar U.S. economy, in addition to most of the observed gender convergence.
hdl:11250/3177155
Keywords: C32; E10; E13; J2; 330; Economic growth; gender inequality; labor market; productivity; VAR with common trends